Heat Shock Protein 70 Is Associated With Cardioversion Outcome and Recurrence of Symptomatic Recent Onset Atrial Fibrillation in Hypertensive Patients. Issue 3 (March 2021) - Rigopoulos, Angelos G.; Kalogeropoulos, Andreas S.; Tsoporis, James N.; Sakadakis, Eleftherios A.; Triantafyllis, Andreas S.; Noutsias, Michel; Gupta, Sahil; Parker, Thomas G.; Rizos, Ioannis
Abstract : Abstract: Accumulating evidence indicates that heat shock proteins (HSPs) may represent a suitable biomarker to predict atrial fibrillation (AF). We investigated the relation of circulating serum HSP70 (sHSP70) with inflammatory cytokines and recurrence of symptomatic recent onset AF (ROAF). We enrolled 90 patients with ROAF (the duration from onset of symptoms ⩽24 hours) and 30 controls. Patients received amiodarone for cardioversion and rhythm control. The association of serum HSP70, serum interleukin-2 (sIL-2), and serum interleukin-4 (sIL-4) with the presence of cardioversion and AF recurrence within a year was investigated. Toll-like receptor 4 (TLR4) signaling dependence for IL-2 and IL-4 induction in response to stimulation with HSP70 was tested in rat aortic vascular smooth muscle cell cultures. Patients had higher sHSP70 and sIL-2 and lower sIL-4 compared with controls. Serum HSP70 was independently associated with ROAF ( P = 0.005) and correlated with sIL-2 (r = 0.494, P < 0.001) and sIL-4 (r = −0.550, P < 0.001). By 48 hours, 71 of the 90 patients were cardioverted, with noncardioverted patients having higher sHSP70 and sIL-2 and lower sIL-4, which were the only independent factors associated with cardioversion. AF recurred in 38 of the 71 cardioverted patients in 1 year. A cutoff value of sHSP70 ≥0.65 ng/mL and sIL-2 ≥0.21 pg/mL was the only independent factor associated with AF recurrence (hazard ratio: 3.311, 95% confidence interval: 1.503–7.293, P = 0.003 and hazard ratio: 3.144, 95% confidence interval: 1.341–7.374, P = 0.008, respectively). The exposure of smooth muscle cell to HSP70 in vitro increased the expression of IL-2 (5×) and IL-4 (1.5×) through TLR4-dependent and receptor-independent mechanisms. In conclusion, sHSP70 and sIL-2 might constitute a prognostic tool for determining the cardioversion and recurrence likelihood in ROAF. Abstract : Supplemental Digital Content is Available in the Text.